2009
DOI: 10.1002/hbm.20845
|View full text |Cite
|
Sign up to set email alerts
|

The effect of presentation paradigm on syntactic processing: An event‐related fMRI study

Abstract: An event-related fMRI study was conducted to investigate the effect of two different sentence presentation paradigms-rapid serial visual presentation (RSVP) and whole sentence presentation-on syntactic processing. During scanning, sentences were presented using one of the two presentation paradigms and were followed by a short delay and a probe to verify sentence comprehension. The delay was included in an attempt to separate sentence-related activity from probe-related activity. The behavioral data showed a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 68 publications
5
21
1
Order By: Relevance
“…Previous fMRI studies that investigated syntactic phrase structure violations reported activations in the left frontal operculum adjacent to BA44 rather than in BA44, in addition to activations in the STG [Brauer and Frederici, 2007;. The left BA44, however, has been shown to be involved in syntactic processing when syntactic complexity was varied [Lee and Newman, 2010;Makuuchi et al, 2009], or when processing demands for sentences with syntactic phrase structure violations increases due to participants' inproficiency in the language [Brauer and Friederici, 2007;Rü schemeyer et al, 2005], or when sentences containing phrase structure violations were randomly mixed with unintelligible sentences [Friederici et al, 2010]. Furthermore, in an fMRI study using visually presented twoword phrases which included a syntactic word category violation, activation was found in the left BA44 as well [Kang et al, 1999].…”
Section: Neural Imprints Of Grammar-based Processesmentioning
confidence: 93%
“…Previous fMRI studies that investigated syntactic phrase structure violations reported activations in the left frontal operculum adjacent to BA44 rather than in BA44, in addition to activations in the STG [Brauer and Frederici, 2007;. The left BA44, however, has been shown to be involved in syntactic processing when syntactic complexity was varied [Lee and Newman, 2010;Makuuchi et al, 2009], or when processing demands for sentences with syntactic phrase structure violations increases due to participants' inproficiency in the language [Brauer and Friederici, 2007;Rü schemeyer et al, 2005], or when sentences containing phrase structure violations were randomly mixed with unintelligible sentences [Friederici et al, 2010]. Furthermore, in an fMRI study using visually presented twoword phrases which included a syntactic word category violation, activation was found in the left BA44 as well [Kang et al, 1999].…”
Section: Neural Imprints Of Grammar-based Processesmentioning
confidence: 93%
“…This study combines data from three separate studies with overlapping stimuli (Lee & Newman, 2010; Newman et al, 2009, 2010); the non-overlapping stimuli were treated as fillers of no interest. Each study was composed of three sessions, training, imaging and debriefing sessions.…”
Section: 0 Methodsmentioning
confidence: 99%
“…Such “reading for meaning” adds layers of complexity such as syntax and grammar. Efforts are underway to study these other components of reading (Yarkoni et al, 2008; Lee and Newman, 2010) while being able to measure task compliance via a measured response. Yet, designing and implementing experimental paradigms that can both present such complex stimuli in a controlled way and allow for the attribution of neural responses to particular parts of these stimuli is non-trivial.…”
Section: Discussionmentioning
confidence: 99%